THE INFLUENCE OF TAX INCENTIVES, TAXPAYER AWARENESS AND TAX SERVICE QUALITY ON UMKM TAXPAYER COMPLIANCE DURING THE PANDEMIC (Case Study on SME Taxpayers in the Subang Region) - Intan Cynthia; Indah Umiyati; Asep Kurniawan (Journal of Taxation Analysis and Review, 2022)
This study aims to determine the effect of tax incentives, taxpayer awareness and quality of tax services on MSME taxpayer compliance during the pandemic in the Subang area. This study uses quantitative methods. The data source of this research is the primary data source. Types of primary data using a questionnaire. This questionnaire was given to MSME taxpayers in the Subang area. Based on the sampling method, it uses quota sampling with a total of 102 respondents. The results show that tax incentives have no effect on taxpayer compliance, taxpayer awareness affects taxpayer compliance, tax service quality affects taxpayer compliance, tax incentives, taxpayer awareness, tax service quality affects taxpayer compliance.